# Difference between revisions of "1969 Canadian MO Problems/Problem 2"

m |
|||

(3 intermediate revisions by 2 users not shown) | |||

Line 7: | Line 7: | ||

<math>\sqrt{c+1}-\sqrt c=\frac{(\sqrt{c+1})^2-(\sqrt c)^2}{\sqrt{c+1}+\sqrt{c}}=\frac1{\sqrt{c+1}+\sqrt{c}}.</math> | <math>\sqrt{c+1}-\sqrt c=\frac{(\sqrt{c+1})^2-(\sqrt c)^2}{\sqrt{c+1}+\sqrt{c}}=\frac1{\sqrt{c+1}+\sqrt{c}}.</math> | ||

− | Similarly, <math>\sqrt c-\sqrt{c-1}=\frac{1}{\sqrt c | + | Similarly, <math>\sqrt c-\sqrt{c-1}=\frac{1}{\sqrt c+\sqrt{c-1}}</math>. We know that <math>\frac1{\sqrt{c+1}+\sqrt{c}}<\frac{1}{\sqrt c+\sqrt{c-1}}</math> for all positive <math>c</math>, so <math>\sqrt{c+1}-\sqrt c <\sqrt c-\sqrt{c-1}</math>. |

− | + | {{Old CanadaMO box|num-b=1|num-a=3|year=1969}} | |

− | {{CanadaMO box |